Mobile-Based Document and Salary Application Case Study: Kemenag Labuhan Batu - Raissa Amanda Putri; Anggun Monica Dewi (Sean Institute, 2021)
The mobile-based document information system is an information system that provides secure document archiving, which is specially designed for android smartphone devices. The purpose and reason for the design of this mobile-based document archive application information system is to store important files safely from disasters that come suddenly, do not fill the room, avoid file loss, can facilitate the work of staff, employees and heads of affairs in needing files. suddenly when employees, staff and heads of affairs are carrying out tasks outside the city. In the design of this mobile-based document archive application information system, two methods are used, namely the data collection method and the Waterfall method in system development. The use of this system will be taken to the main page which directs the archivist and head of affairs to login first before archiving documents and downloading documents wherever they are. The application is made to provide safe storage of documents from disasters that result in document damage, does not fill the administrative room with documents and the main thing is to make it easier for employees, staff and heads of affairs when they need documents suddenly.